EDUCATION GAME IN ENGLISH LEARNING CENTER OF ENGLISH IS EASY - Sang Ayu Made Krisna Dewi Natalia; I Gede Arief Aditya; I Nyoman Agus Suarya Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2019)
English is the most used international language in the world for communication. Thus, many private companies take part in teaching English. One of the institutions that facilitate English learning is English Learning Center EC (English is Easy). However, in teaching and learning process, it is necessary to have companion media that suitable with current condition, that is education game application with English materials in English Learning Center EC (English is Easy). Data collection used interview and observation methods. According to testing result, game has been suitable with the concept and plan. Game also gets positive feedback from the students who played it.